2021
DOI: 10.1186/s12885-021-07932-3
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cytokines as biomarkers of oral cancer: a systematic review and meta-analysis

Abstract: Background Oral cancer (OC) is usually diagnosed at advanced clinical stages due to its asymptomatic nature and absence of pathognomonic signs in its early development phase. Delayed diagnosis is one of the major causes of OC treatment failure and poor prognosis. Development of alternative diagnostic approaches are imperative for improving early detection and therapeutic success rates. Salivary cytokines (SC) have been studied as potential diagnostic biomarkers for OC and may represent a potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…In Marques, et al's study, they found an increase in IFN-g, IL-10, IL-17, IL-1b, IL-6, and IL-4 in SLE patients without periodontal disease compared to HC (136). Also in a meta-analysis, IL-8, IL-1b, TNF-a, IL-6, and IL-1a were found to be increased in oral cancer compared to HC and leukoplakia and were suggested as cancer biomarkers (137) In our study, the significant differences between HC and BD-MQ is an important finding to be able to differentiate the levels of cytokines present in "normal" saliva content and orally asymptomatic BD patients saliva. Increased detection of IL-8, IL-1b, and TNF-a may not be specific to BD for diagnostics, but can still be useful to monitor the level of oral inflammation in order to deter further ulcerations, and potentially, accompanying systemic manifestations.…”
Section: Saliva As a Biomarker For Diagnosis And Disease Progressionmentioning
confidence: 92%
“…In Marques, et al's study, they found an increase in IFN-g, IL-10, IL-17, IL-1b, IL-6, and IL-4 in SLE patients without periodontal disease compared to HC (136). Also in a meta-analysis, IL-8, IL-1b, TNF-a, IL-6, and IL-1a were found to be increased in oral cancer compared to HC and leukoplakia and were suggested as cancer biomarkers (137) In our study, the significant differences between HC and BD-MQ is an important finding to be able to differentiate the levels of cytokines present in "normal" saliva content and orally asymptomatic BD patients saliva. Increased detection of IL-8, IL-1b, and TNF-a may not be specific to BD for diagnostics, but can still be useful to monitor the level of oral inflammation in order to deter further ulcerations, and potentially, accompanying systemic manifestations.…”
Section: Saliva As a Biomarker For Diagnosis And Disease Progressionmentioning
confidence: 92%
“…Several studies have evaluated blood and saliva cytokines in head and neck squamous cell carcinomas. Recent studies found different salivary levels of some cytokines among oral cancer, OPMD, and healthy patients, suggesting these cytokines as potential diagnostic biomarkers for oral cancer and OPMD [ 12 ]. Rhodus et al studied levels of proinflammatory, angiogenic, NF-kB dependant cytokines IL-1, IL-6, IL-8, and TNF-a in whole stimulated saliva and showed that these were significantly elevated in OSCC patients compared to subjects with oral premalignant disorders (OPMD) and controls [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, several reviews, which summarize and analyze the evidence of salivary cytokines as potential OSCC biomarkers, have been published [26,60,61]. The most distinguishing aspects that differentiate the present review from those works are: (1) the inclusion of longitudinal prospective studies, in which subjects are followed over time with repeated cytokine level monitoring; (2) the inclusion of studies investigating the cytokine level discriminatory power to distinguish early from advanced OSCC stages; and (3) the inclusion of several studies that use multiplex immunoassays to simultaneously quantify several salivary cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%